2019
DOI: 10.1097/mcg.0000000000001272
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Deep-learning Polyp Detection System in Prospectively Collected Colonoscopy Videos With Variable Bowel Preparation Quality

Abstract: Background: Colonoscopy is the gold standard for polyp detection, but polyps may be missed. Artificial intelligence (AI) technologies may assist in polyp detection. To date, most studies for polyp detection have validated algorithms in ideal endoscopic conditions. Aim: To evaluate the performance of a deep-learning algorithm for polyp detection in a real-world setting of routine colonoscopy with variable bowel preparation quality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…This technique facilitates the development of ML algorithms based upon relevant patient outcomes. detection [2][3][4][5][6] and classification of polyps based on their predicted histology [7][8][9]. However, additional ML techniques would benefit from a tight linkage of colonoscopy videos with patient-level data.…”
Section: Discussionmentioning
confidence: 99%
“…This technique facilitates the development of ML algorithms based upon relevant patient outcomes. detection [2][3][4][5][6] and classification of polyps based on their predicted histology [7][8][9]. However, additional ML techniques would benefit from a tight linkage of colonoscopy videos with patient-level data.…”
Section: Discussionmentioning
confidence: 99%
“…However, the threshold required for reporting FPs is unsettled. One report suggested that only FPs > 2 s be reported [ 13 ], and another only reported FPs > 1 s [ 15 ], while the majority of FPs (i.e., more than 90%) lasted <0.5 s [ 13 ]. It is unknown whether ignoring the transient FPs (i.e., those lasting for <1 or 2 s) would increase the risk of missing a real polyp.…”
Section: Definition Of False Positivesmentioning
confidence: 99%
“…The definition of the presence of an FP is dependent on the judgment of the endoscopist. For studies analyzing CADe-overlaid videos, FPs were judged by a single expert reader or through the consensus of 2–3 reviewers [ 12 , 15 , 18 ]. Thus, there is room for errors due to subjectivity in these definitions.…”
Section: Definition Of False Positivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A vastagbéltükrözést számos úton tudják támogatni a kü lönböző AIrendszerek. Egyrészt az emberi hibából adódó tévedések csökkentésében, az elnézett polipok számának csökkentésében (20), akár különböző béltisztasági fok ese tén is (21), amely fontos minőségi szempont vastagbéltük rözés során. Másrészt a polip elnézési arány csökkentésében, a polipdetekció javításában és a felismerés pontosításában, a felismert polipok klasszifikációjában (22,23), valamint a szövettani eredmény előzetes becslésében (24,25).…”
Section: Vastagbélunclassified